Revision Surgeries After Proton vs Photon Postmastectomy Radiation Therapy in Prepectoral Implant-Based Breast Reconstruction - Desai, Anshumi; Mangal, Rohan; Padilla, Carolina; McClintock, Kate; Choi, Seraphina; Mella-Catinchi, Juan R; Oeltjen, John C; Singh, Devinder P; Takita, Cristiane; Kassira, Wrood (Aesthetic surgery journal, 2025)
Postmastectomy radiation therapy (PMRT) improves disease-free survival in breast cancer but reduces aesthetic satisfaction. Proton PMRT has gained popularity because it results in fewer systemic complications. There is a lack of data regarding revision surgeries for prepectoral implant-based breast reconstruction (PP-IBBR) following radiation. The aim of this study was to compare revision surgeries in PP-IBBR with photon vs proton PMRT. A single-institution retrospective cohort study was performed that included breast cancer patients undergoing mastectomy and PP-IBBR with PMRT between January 2020 and October 2022. The mean follow-up duration for the cohort was 1056.4 days (2.89 years). Revision surgeries evaluated were fat grafting, conversion to autologous flaps, implant replacement, implant removal, capsulectomy, and scar revision. The 116 PP-IBBR subjects were divided into 2 cohorts, receiving either photon (75, 64.66%) or proton (41, 35.34%) radiation. Overall corrective surgeries were higher with photon therapy (27.5% overall; 32.4% photon vs 19.5% proton, P = .132). The odds of any revision surgery were nearly double with photon therapy (odds ratio [OR] = 1.98), and the conversion to an autologous flap was significantly more likely with photon therapy (OR = 4.55, P = .025). Multivariable analysis showed an increased tendency for photon therapy patients to require any revision surgeries (OR = 1.62, P = .359), autologous flaps (OR = 5.97, P = .049), fat grafting (OR = 1.52, P = .664), and scar revision (OR = 4.51, P = .273). Compared to proton therapy, traditional photon therapy has a higher conversion rate to autologous flaps with PP-IBBR. Photon therapy had higher rates of overall revision surgeries, but the difference was not statistically significant. Proton therapy is safer and requires fewer revision surgeries, warranting larger studies and broader utilization.